2017
DOI: 10.1007/s11064-017-2183-2
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophic Effect of Asiatic acid, a Triterpene of Centella asiatica Against Chronic 1-Methyl 4-Phenyl 1, 2, 3, 6-Tetrahydropyridine Hydrochloride/Probenecid Mouse Model of Parkinson’s disease: The Role of MAPK, PI3K-Akt-GSK3β and mTOR Signalling Pathways

Abstract: Regulation of various signalling (Ras-MAPK, PI3K and AKT) pathways by augmented activity of neurotrophic factors (NTFs) could prevent or halt the progress of dopaminergic loss in Parkinson's disease (PD). Various in vitro and in vivo experimental studies indicated anti-parkinsonic potential of asiatic acid (AA), a pentacyclic triterpene obtained from Centella asiatica. So the present study is designed to determine the neurotrophic effect of AA against 1-methyl 4-phenyl 1, 2, 3, 6-tetrahydropyridine hydrochlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 47 publications
3
22
0
Order By: Relevance
“…It dissolves in methanol, ethanol, and water. Relevant literature on the nervous system demonstrated that C. asiatica and its triterpenes could be used to relieve a variety of neurological diseases, but the most researched are improve Alzheimer's disease (AD) (Song et al, 2018) and Parkinson's disease (Nataraj et al, 2017b) (Table 2). The pathogenesis of AD and Parkinson's disease involve neuroinflammatory activities (Gelders et al, 2018), oxidative stress (Jiang et al, 2016), mitochondrial dysfunction (Morais and De Strooper, 2010), and dysfunction in brain-derived neurotrophic factor (Mohammadi et al, 2018).…”
Section: Effects On Neurological Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…It dissolves in methanol, ethanol, and water. Relevant literature on the nervous system demonstrated that C. asiatica and its triterpenes could be used to relieve a variety of neurological diseases, but the most researched are improve Alzheimer's disease (AD) (Song et al, 2018) and Parkinson's disease (Nataraj et al, 2017b) (Table 2). The pathogenesis of AD and Parkinson's disease involve neuroinflammatory activities (Gelders et al, 2018), oxidative stress (Jiang et al, 2016), mitochondrial dysfunction (Morais and De Strooper, 2010), and dysfunction in brain-derived neurotrophic factor (Mohammadi et al, 2018).…”
Section: Effects On Neurological Diseasesmentioning
confidence: 99%
“…The concentration of this factor is reduced in the brain of patients with neurodegenerative diseases (Lima Giacobbo et al, 2019). C. asiatica extract, asiatic acid, and (Gopi and Arambakkam Janardhanam, 2017;Nataraj et al, 2017b;Chintapanti et al, 2018;Boondam et al, 2019). C. asiatica and its triterpenoids affect neurological diseases possibly through the mitogen-activated protein kinase (MAPK) signaling pathway, phosphotidylinositol 3 kinase/protein kinase B/ mammalian target of rapamycin (PI3K/Akt/mTOR)signaling pathway, and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB) signaling pathway ( Table 2).…”
Section: Effects On Neurological Diseasesmentioning
confidence: 99%
“…Parkinson's disease [47] Citrus grandis Alzheimer's disease [73,78,80,290] cholinesterase, and to directly or allosterically bind to the GABAergic system; all with a relation to disorders like anxiety, insomnia, convulsion, pain, and cognitive deficits [25].…”
Section: Asiatic Acid Prevent Mptp/p-induced Neuronal Cells Lossmentioning
confidence: 99%
“…Krishnamurthy et al (14) reported that asiatic acid (AA), a tri-terepene of CA could transverse the blood-brain barrier and mitigated mitochondrial injury in a mouse model of focal cerebral ischemia. Many previous studies revealed that this compound was a potent protective agent for brain against various neurotoxins (15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%